Body, education and culture with teenagers in formation. Learning to learn and the experiences of the Afro-Brazilian Art Center of the University of São Paulo (Revista de Cultura e Extensão USP, 2017)
The following text presents some interwoven provocations that arise from wisdom and experiences of Contramestre Pinguim taken here as opportunities to think about culture as mediator of public policies for education at school. We start with a panorama of the appropriation of “doing culture” in the city by young people by promoting autonomous and non institutionalized artistic-cultural movements that gained force in the two last decades, most of them in the peripheries of São Paulo where there is a critical death rate among black young people as consequence of violence. Next we present the Afro-Brazilian Art Center of the University of São Paulo as an artistic-cultural occupation, with political outcomes, since 1997. We approach its extensional concept and some of its actions not to present them as complete models, but as educational proposals in constant construction process in order to enrich the debates on “Education and University from the point of view of Culture and Extension” in the hope of the creation of affirmative university policies for interaction with school communities. Among these experiences we highlight a narrative about the participation of researchers from the Afro-Brazilian Art Center as art educators at the FEBEM (Foundation for Minors Welfare – a youth detention center), which is now called Casa Foundation.